Effects of transmission-blocking vaccines simultaneously targeting pre- and post-fertilization antigens in the rodent malaria parasite Plasmodium yoelii. Issue 1 (December 2016) - Zheng, Li; Pang, Wei; Qi, Zanmei; Luo, Enjie; Cui, Liwang; Cao, Yaming
Abstract Background Transmission-blocking vaccine (TBV) is a promising strategy for interrupting the malaria transmission cycle. Current TBV candidates include both pre- and post-fertilization antigens expressed during sexual development of the malaria parasites. Methods We tested whether a TBV design combining two sexual-stage antigens has better transmission-blocking activity. Using the rodent malaria modelPlasmodium yoelii, we pursued a DNA vaccination strategy with genes encoding the gametocyte antigen Pys48/45 and the major ookinete surface protein Pys25. Results Immunization of mice with DNA constructs expression either Pys48/45 or Pys25 elicited strong antibody responses, which specifically recognized a 45 and 25 kDa protein from gametocyte and ookinete lysates, respectively. Immune sera from mice immunized with DNA constructs expressing Pys48/45 and Pys25 individually and in combination displayed evident transmission-blocking activity in in vitro ookinete culture and direct mosquito feeding experiments. With both assays, the Pys25 sera had higher transmission-blocking activity than the Pys48/45 sera. Intriguingly, compared with the immunization with the individual DNA vaccines, immunization with both DNA constructs produced lower antibody responses against individual antigens. The resultant immune sera from the composite vaccination had significantly lower transmission-blocking activity than those from Pys25 DNA immunization group, albeit the activity was substantially higher than that from the Pys48 DNA vaccination group. Conclusions This result suggested that vaccination with the two DNA constructs did not achieve a synergistic effect, but rather caused interference in inducing antigen-specific antibody responses. This result has important implications for future design of composite vaccines targeting different sexual antigens.